Dr. Hans Max Hirschfeld, man zonder moreel kompas? Over de ontsporing van beeldvorming - Bruin, R. de (BMGN - Low Countries Historical Review, 2008)
Dr Hans Max Hirschfeld: A Man without a Moral Compass? On Dislodging PerceptionsEven though his father was Jewish, Hans Max Hirschfeld became one of the most prominent Dutch civil servants during the German Occupation of the Netherlands. In the interest of the Dutch population, Hirschfeld was supposed to co-operate with the German Reichskommissariat. However, various measures made him very unpopular with the government in exile and the resistance movement. In his well-read history of the Netherlands under Nazi rule, Dutch historian Loe de Jong portrayed Hirschfeld as the personification of the aloofness that was characteristic of many Dutch people with regard to the persecution of the Jews. De Jong characterized Hirschfeld as a typical ‘negotiator’, who had learned to shield his emotions regarding the fate of the Jews. In the past few years, two biographies on Hirschfeld have been published, in which De Jong’s characterizations play a major role. This article, based on research of De Jong’s records, claims that the characterizations were largely inventions of De Jong, rooted in images projected in the illegal press during the German Occupation. This review is part of the discussion forum 'Dr. Max Hirschfeld. Man van het grote geld' (Meindert Fennema en Johan Rhijnsburger).